White blood cell counts can predict 4-year cardiovascular disease risk in patients with stable coronary heart disease: a prospective cohort study - Jiang, Wencai; Huang, Gang; Du, Jinfeng; Yang, Hanxuan; Zhou, Shiheng; Dai, Dayin; Tang, Kai; Fang, Lingxiao; Wang, Xiao; Deng, Xuejun (Frontiers in Cardiovascular Medicine, 2024)
Background The prevalence of cardiovascular disease has increased sharply in the Asian population, and evaluation of the risk of cardiovascular events with stable coronary heart disease remains challenging. The role of white blood cell (WBC) count in assisting clinical decision-making in this setting is still unclear. Objectives This study sought to evaluate the prognostic meaning of WBC count among patients with stable coronary heart disease. Methods This study included Asian participants (n = 1,933) from the prospective STABILITY (Stabilization of Atherosclerotic Plaque by Initiation of Darapladib Therapy) trial, which involved 15,828 patients with stable coronary heart disease with 3–5 years of follow-up on optimal secondary preventive treatment. WBC count was measured at baseline. Associations between WBC count and cardiovascular outcomes were evaluated by Cox regression analyses with multivariable adjustments. Hematologic emergencies in patients may introduce potential bias. Results In the lower WBC count quartiles, patients had lower-risk clinical profiles. Higher WBC counts were associated with greater event probabilities for cardiovascular death, major cardiovascular events, or all-cause death. In Cox regression models, WBC counts were an independent predictor of major adverse cardiovascular events (OR = 2.445, 95% CI 1.427–4.190, P = 0.001) for the primary outcomes. For the secondary outcomes, including the composite of all-cause death, cardiovascular death, myocardial infarction, stroke, and hospitalization for heart failure, WBC counts were significantly predictive of events with similar magnitude (OR = 1.716, 95% CI 1.169–2.521, P = 0.006). Conclusions In patients with stable coronary heart disease, higher WBC counts were associated with a heightened risk for the primary or secondary outcomes. Registration https://clinicaltrials.gov/; Unique identifier NCT00799903.